Precious corals (Coralliidae) from north-western Atlantic Seamounts - Simpson, Anne; Watling, Les (JOURNAL OF THE MARINE BIOLOGICAL ASSOCIATION OF THE UNITED KINGDOM, 2011)
Two new species belonging to the precious coral genus Corallium were collected during a series of exploratory cruises to the New England and Corner Rise Seamounts in 2003-2005. One red species, Corallium bathyrubrum sp. nov., and one white species, C. bayeri sp. nov., are described. Corallium bathyrubrum is the first red Corallium to be reported from the western Atlantic. An additional species, C. niobe Bayer, 1964 originally described from the Straits of Florida, was also collected and its description augmented.
Keywords: HOV Alvin (Human Occupied Vehicle)